DINÁMICA DE LA INFECCIÓN CON Mycoplasma hyopneumoniae EN PORCINOS PROVENIENTES DE MADRES CON Y SIN ANTECEDENTES DE INMUNIZACIÓN - Bachmann C., Vanessa (2006)
The aim of the study was to determine the time of infection with Mycoplasma hyopneumoniae in 240 piglets of vaccinated and non vaccinated sows from a positive farm with an all-in/all-out (AIAO) system, located in the Chillón valley, Lima. The study was conducted during autumn and winter 2003. One group of sows was vaccinated with 2 ml of a M. hyopneumoniae commercial bacterin at 85 days of gestation while the other group remained unvaccinated. Two groups of 120 piglets each were established according to their dams’ status of immunity. Blood samples were collected from piglets at various times during the production period (weaning till slaughter) for measuring antibodies against M. hyopneumoniae using an ELISA indirect assay. The 66.6 (74/112) and 85.6% (101/118) of piglets from the vaccinated and non-vaccinated dams, respectively, were seroreactive throughout the period of the study. The results indicated that the time of infection occurred in both groups at approximately 10 weeks of age, and without significant differences between groups (p>0.05). Time of infection occurred concomitantly with the stress caused by the relocation of piglets from nursery to growth-finishing corrals